Inspiration strikes: Partnering with experienced student consultants to prepare to partner with new student consultants - Chaiet, Donna; Chasen, Karen (International Journal for Students as Partners, 2024)
This article examines the process of partnering with experienced undergraduate SaLT consultants to ready educators to work in partnership with high school student consultants. We discuss the benefits of preparation: giving time to building relationships, being ready to receive feedback, learning to trust the process of student partnership, and honoring authenticity and vulnerability.